Effects of snow persistence on soil water nitrogen across an elevation gradient - Anenberg, Alyssa Nicole, author; Kampf, Stephanie, advisor; Baron, Jill, advisor; Borch, Thomas, committee member (Colorado State University. Libraries, 2019)
In the western United States, the timing and magnitude of snowmelt is an important control on soil water and nutrient availability. Warming trends can alter the timing of snowmelt, directly impacting snow cover and soil freeze-thaw cycles, as well as available water for downstream use. While prior research relating snow to soil water nitrogen has focused on areas with persistent winter snow, the snow and soil water dynamics in lower elevation areas with intermittent snowpack are not as well documented. The broad goal of this study is to understand how the duration of snow persistence affects soil moisture and soil water nitrogen concentrations. The specific objectives are to address (1) how the duration of snow persistence affects soil moisture across an elevation gradient, from areas where the snowpack ranges from shallow and intermittent to deep and persistent throughout the winter and (2) how this gradient in snowpack affects soil water nitrogen. Three study sites that span a 1500m elevation gradient were established in the Colorado Front Range to monitor snow, soil moisture, and soil water nitrogen. The highest elevation site, Michigan River, is located in the persistent snow zone; the middle elevation site, Dry Creek, is in the transitional snow zone; and the lowest elevation site, Mill Creek, lies in the intermittent snow zone. Each site was equipped with soil moisture probes at 5 and 20cm depth, soil temperature probes, snow depth poles monitored by time-lapse cameras, and ion exchange resin probes. The Mill Creek research site also contained nine snow manipulation chambers and twenty-seven tension lysimeters to sample soil water nitrogen. Snow cover persisted for longer periods of time as elevation increased and soil temperatures decreased. Lower elevation sites were consistently warmer and drier than the higher elevation site. At the highest elevation site, soil moisture increased after a large pulse of snowmelt in the late spring, while the lower elevations experienced multiple smaller pulses of soil moisture following individual snow events. In the snow manipulation chambers, plots with increased snow depth experienced increased soil moisture, however plots with decreased snow depth did not always produce the lowest soil moisture. Additionally, soil moisture in the control snow plots and in plots with increased snow depth consistently increased throughout the melt season, whereas plots with decreased snow depth briefly increased after each snowmelt event then declined to pre-event levels. NO₃– and NH₄+ were correlated with soil moisture, and large increases in soil moisture were associated with a flushing signal of NO₃–. This suggests that soil water nitrogen is regulated by the amount of soil water available, and that nitrogen can be impacted when changes in snow alter soil moisture timing and magnitude.
Keywords: nitrogen; snowmelt; soil water; snow; nitrate; snow persistence